Continuous Integration and Continuous Delivery Platform Development of Software Engineering and Software Project Management in Higher Education - Sendy Ferdian; Tjatur Kandaga; Andreas Widjaja; Hapnes Toba; Ronaldo Joshua; Julio Narabel (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
We present a report of development phase of a platform which aims to enhance the efficiency of software project management in higher education. The platform accommodates a strategy known as Continuous Integration and Continuous Delivery (CI/CD). The phase consists of several stages, followed by testing of the system and its deployment. For starters, the CI/CD platform will be deployed for software projects of students in the Faculty of Information Technology, Universitas Kristen Maranatha. The goal of this paper is to show a design of an effective platform for continuous integration and continuous delivery pipeline to accommodate source code compilation, code analysis, code execution, until its deployment, all in a fully automated fashion.